Separation of Anthalona gen.n. from Alona Baird, 1843 (Branchiopoda: Cladocera: Anomopoda): morphology and evolution of scraping stenothermic alonines - Damme, Kay Van; Sinev, Artem Yu; Dumont, Henri J. (Zootaxa, 2011)
We move the freshwater cladocerans Alona verrucosa Sars, 1901 and related species from the lump genus Alona Baird, 1843 (Anomopoda: Chydoridae: Aloninae) to Anthalona gen. n. We revise the group and describe five new taxa from tropics and subtropics: Anthalona simplex n. sp., DR Congo, A. harti n. sp., Africa (with two subspecies), A. acuta n. sp., Brazil and A. obtusa n. sp., Borneo. Anthalona is a genus of relatively small-sized, stenothermic Aloninae with specializations for scraping. Within the subfamily, the new genus is closest to Karualona and Coronatella. We discuss possible homoplasy of limb characters between latter and Anthalona. The genus can be considered an important case study in an evolutionary trend towards oligomerization of limb structures at low taxonomical levels and within an extant crustacean lineage. Composition of the genus reflects a complex history. Species with unusual morphologies (A. brandorffi, A. simplex n. sp.) appear basal in our phylogeny and may be relicts, in comparison to a pantropical A. verrucosa complex of similar forms. Several species may coexist in a single water body such as A. acuta n. sp. and A. verrucosa in the Neotropics, suggesting niche separation.